Synthesis of Stable 1H-Azirines Reinvestigated: A Structural Corrigendum - Banert, Klaus; Hagedorn, Manfred; Peisker, Heiko (Synlett, 2012)
The isoquinoline-catalyzed synthesis of pretended 1H-azirines from phenacyl bromides and N,N′-dialkylcarbodiimides was repeated. The products do not possess the structure of antiaromatic 1H-azirines, but simple N-acyl-N,N′-dialkylureas were formed instead. This structural corrigendum was confirmed by the independent synthesis of the known ureas and comparison of their 1H NMR and 13C NMR spectroscopic data in the case of six compounds. Thus, 1H-azirines keep their classification as very short-lived intermediates.
Keywords: acylation; antiaromatic heterocycles; structure; assignment by spectroscopy; ureas